PENGARUH PENGGUNAAN MODEL PEMBELAJARAN QUICK ON THE DRAW TEHADAP MOTIVASI BELAJAR PPKn SISWA KELAS VII DI SMP NEGERI 1 PANGKALAN KURAS KABUPATEN PELALAWAN - Enalia, Enalia; Erlinda, Sri; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is based on the low motivation of learning PPKn students class VII in SMP Negeri 1 Pangkalan Kuras Kabupaten Pelalawan. The formulation of the problem in this research is "Is there any significant effect of using Quick On The Draw learning model toward students’ motivation in learning PPKn at SMP Negeri 1 Pangkalan Kuras Kabupaten Pelalawan?". This study aims to determine the effect of using Quick On The Draw learning model toward students’ motivation in learning PPKn at SMP Negeri 1 Pangkalan Kuras Kabupaten Pelalawan. This research was conducted at SMP Negeri 1 Pangkalan Kuras Kabupaten Pelalawan in April 2018. This research was a quantitative descriptive study that was experimental. Population in this study were students of class VII SMP Negeri 1 Pangkalan Kuras Kabupaten Pelalawan. The sample in this research was taken based on "Random Sampling" technique. Where the class taken into the sample was the students of class VII F (experimental class) who were given the Quick On The Draw learning model, and class VII G (control class) were students who were given the conventional method. Then data analysis by using homogeneity test and "t" test. Based on the result of research indicated that there wasan effect of learning motivation between student who using Quick On The Draw learning model and conventional method in SMP Negeri 1 Pangkalan Kuras Kabupaten Pelalawan ( > ).Where there was an average increase toward motivation in learning PPKn of experimental class from 20,48  to 24,96 and the average of PPKn learning motivation of control class from 19,23 to 21,56. Thus the hypothesis which reads that there is an effect of using Quick On The Draw learning model toward learning motivation of PPKn student at SMP Negeri 1 Pangkalan Kuras Kabupaten Pelalawan, can be accepted. Key Words : Quick On The Draw, Motivation